Influence of diet on oxidative DNA damage, uracil misincorporation and DNA repair capability - Prado, Renato Paschoal [UNESP]; Santos, Bruna Fornazari dos [UNESP]; Pinto, Carla Lombardi de Souza [UNESP]; Assis, Katia Regina Carvalho de [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Ladeira, Marcelo Sady Placido (Oxford University Press, 2010)
The contribution of diet to cancer ranges from 10 to 80%. The low ingestion of antioxidants and enzymatic cofactors involved in DNA repair and methylation reactions and the high ingestion of chemical additives present in the modern diet, associated with genetic factors, could lead to genomic instability and the hypomethylation of proto-oncogenes, thus contributing to development of genetic-related diseases such as cancer. The present study evaluated the influence of diet on the level of oxidative DNA damage, misincorporated uracil and DNA repair capability in peripheral blood lymphocytes from two groups of individuals with antagonist diets as follows: (i) 49 healthy individuals with a diet rich in organic products, whole grains, fruit and vegetables and poor in processed foods (Group I) and (ii) 56 healthy individuals with diet rich in processed foods and poor in fruit and vegetables (Group II). Oxidative DNA damage, uracil incorporation and DNA repair capability were assessed by the comet assay. The individuals in Group I presented lower levels of oxidative DNA damage (oxidized purines and pyrimidines) and lower levels of DNA damage induced by ex vivo treatment with hydrogen peroxide (H(2)O(2)) than those individuals in Group II. The analysis of our results suggests that a diet rich in organic products, integral grains, fruit and vegetables and poor in industrialized products can protect against oxidative DNA damage and DNA damage induced by H(2)O(2).